PURCHASE INTENTION TOWARDS FASHION COUNTERFEIT PRODUCTS - , ALBERTUS INDRA PRATAMA, Prof. Dr. Basu Swastha Dharmmesta, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Threat of counterfeiting is expanding globally and rapidly, it is cause by the improvement of technology, less control from the government and also increasing demand for counterfeit products. Counterfeit product not only causing loss to the government and the original manufacturer, but also damaging the brand image and causing societal problem. This research focusing in fashion counterfeits products and the purchase intention towards it, from the consideration of ethical dilemma and perceived risk. The analysis of this research used multiple regression find the relationship of Idealism, Relativism, General uncertainty about consequences, uncertainty about symbolic performance, uncertainty about physical appearance, and uncertainty about durability with the intention to purchase fashion counterfeit products. The samples were 210 respondents conducted using online survey. The result showed that Idealism and General uncertainty about consequences are important issues to be considered in purchasing fashion counterfeit products.